KEOPS complex promotes homologous recombination via DNA resection. Issue 11 (2nd April 2019) - He, Ming-Hong; Liu, Jia-Cheng; Lu, Yi-Si; Wu, Zhi-Jing; Liu, Ying-Ying; Wu, Zhenfang; Peng, Jing; Zhou, Jin-Qiu
Abstract: KEOPS complex is one of the most conserved protein complexes in eukaryotes. It plays important roles in both telomere uncapping and tRNA N 6 -threonylcarbamoyladenosine (t 6 A) modification in budding yeast. But whether KEOPS complex plays any roles in DNA repair remains unknown. Here, we show that KEOPS complex plays positive roles in both DNA damage response and homologous recombination-mediated DNA repair independently of its t 6 A synthesis function. Additionally, KEOPS displays DNA binding activity in vitro, and is recruited to the chromatin at DNA breaks in vivo, suggesting a direct role of KEOPS in DSB repair. Mechanistically, KEOPS complex appears to promote DNA end resection through facilitating the association of Exo1 and Dna2 with DNA breaks. Interestingly, inactivation of both KEOPS and Mre11/Rad50/Xrs2 (MRX) complexes results in synergistic defect in DNA resection, revealing that KEOPS and MRX have some redundant functions in DNA resection. Thus we uncover a t 6 A-independent role of KEOPS complex in DNA resection, and propose that KEOPS might be a DSB sensor to assist cells in maintaining chromosome stability.